2008
DOI: 10.1038/nsmb.1515
|View full text |Cite
|
Sign up to set email alerts
|

Defining the TRiC/CCT interactome links chaperonin function to stabilization of newly made proteins with complex topologies

Abstract: Folding within the crowded cellular milieu often requires assistance from molecular chaperones that prevent inappropriate interactions leading to aggregation and toxicity. The contribution of individual chaperones to folding the proteome remains elusive. We here demonstrate that the eukaryotic chaperonin TRiC/CCT (TCP1-Ring Complex or Chaperonin Containing TCP1) has broad binding specificity in vitro similar to the prokaryotic chaperonin GroEL. However, in vivo TRiC substrate selection is not based solely on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
366
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 365 publications
(386 citation statements)
references
References 60 publications
9
366
0
Order By: Relevance
“…A recent study of the TRiC interactome suggests that ~ 10% of newly synthesized cellular proteins, including actin, tubulin, cell cycle regulators and tumor suppressors are TRiC substrates. Generally, multidomain proteins ranging from 40-75 kDa are ideal substrates (Yam et al, 2008). This study also showed that proteins belonging to oligomeric assemblies are highly enriched in the interactome and this suggests a role of TRiC in facilitating protein complex assembly in cells.…”
Section: Ii4113 the Chaperoninssupporting
confidence: 58%
See 1 more Smart Citation
“…A recent study of the TRiC interactome suggests that ~ 10% of newly synthesized cellular proteins, including actin, tubulin, cell cycle regulators and tumor suppressors are TRiC substrates. Generally, multidomain proteins ranging from 40-75 kDa are ideal substrates (Yam et al, 2008). This study also showed that proteins belonging to oligomeric assemblies are highly enriched in the interactome and this suggests a role of TRiC in facilitating protein complex assembly in cells.…”
Section: Ii4113 the Chaperoninssupporting
confidence: 58%
“…Unlike GroEL/ES which can act only post-translationally, TRiC has been shown to fold the discrete domains of firefly luciferase co-translationally (Frydman et al, 1994). From biochemical studies using unfolded firefly luciferase, actin and tubulin, it has been shown that while GroEL/ES failed to fold these model proteins, TRiC was able to mediate their folding, suggesting that it can interact with a different range of substrates via mechanism distinct from class I chaperonins (Frydman et al, 1992;Tian et al, 1995;Yam et al, 2008). A recent study of the TRiC interactome suggests that ~ 10% of newly synthesized cellular proteins, including actin, tubulin, cell cycle regulators and tumor suppressors are TRiC substrates.…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
“…TRiC also appears important for the prevention of protein aggregation and toxicity (6)(7)(8). TRiC is essential for cell viability, as it assists the folding of many essential proteins, including actin, tubulin, and many cell cycle regulators and signaling molecules (9,10). Notably, a number of TRiC substrates cannot be folded by other chaperonins, suggesting that TRiC possesses unique structural and mechanistic properties that distinguish it functionally from other chaperonins (11,12).…”
mentioning
confidence: 99%
“…The open state of the complex binds the polypeptide substrate (4,5), whereupon closing the substrate is sequestered into a large interior cavity where folding can occur. TRiC has been implicated in the folding pathways of many cytosolic proteins (6), most notably actin and tubulin (7,8).…”
mentioning
confidence: 99%